William Blake and the cultures of radical Christianity - Rix, Robert (Ashgate, 2007)
Early contexts and the Moravian tradition -- Libertines, liberators and legislators -- Swedenborgianism -- From Swedenborg to radical politics -- International Swedenborgians in London -- The divine image -- The marriage of heaven and hell as satire -- The visionary marketplace